THE EFFECT OF APPLYING EXAMPLES NON EXAMPLES METHOD ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Astri Khoirun Nissa; Sri Juriati Ownie (Universitas Negeri Medan, 2015)
This study is aimed to find out whether Examples Non Examples method significantly effects the students’ achievement in writing descriptive text. This study was an experimental design. The population of the study was grade VIII of SMP Swasta Siti Hajar. There were two classes as the sample and each class consisted of 30 students. The classes were divided into two groups, namely Experimental and Control group. Experimental group was the class taught by applying Examples Non Examples method, while Control was taught without using Examples Non Examples method. In this study, writing test was used as the instrument of collecting the data. Both experimental and control group were asked to write descriptive paragraph in pre-test and post-test. The data obtained were analyzed statistically by t-test formula. The result got that t-observed (t-obs) is higher than t-table (2.64 > 2.042) at the level significance 0.05 with the degree of freedom (df) 58. It means that the alternative hypothesis (Ha) is accepted and Examples Non Examples method significantly effects students’ achievement in writing descriptive text.